Analysis of the Use of Tenses in English Theory and Practice - Kasari, Khairin; Lubis, Yani; Andriani, Septria; Marzuky, Mhd Sulung (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
Tenses is the primary component of the English language sentence structure that indicates the duration of a particular study. The purpose of this article is to analyze the various types of tenses, their functions, and their applications in speaking and writing. Study is conducted through a study of library and a descriptive qualitative analysis of various linguistic source and practical applications. The study's findings indicate that strong tenses comprehension significantly improves communication skills in English. Common problems, such as the use of the simple past and present perfect, are common, especially among EFL (English as a Foreign Language) learners. This article also discusses strategies for improving tenses in spoken language practice.